CRIMINAL PUNISHMENT AS AN EFFORT TO OVERCOME THE CRIMINAL ACT OF RECEIVING GOODS FROM THE PROCEEDS OF THE CRIME OF THEFT OF MOTOR VEHICLES - Santoso, Muhammad Iqbal; Hartanto; Wiryadi, Uyan (International Peneliti Ekonomi, Sosial dan Teknologi, 2025)
The most common criminal law in society is criminal acts against property (material crimes), such as theft, extortion, embezzlement, fraud, vandalism, and receiving. The existence of a receiver as a receiver for theft crimes makes it easy for the perpetrator to gain profit, so that the perpetrator of theft does not have to sell the stolen goods to consumers himself but can channel them through a receiver who pretends to be a trader. The problems that arise are both violations of social norms and legal regulations to create a phenomenon that is contrary to moral and ethical rules and legal regulations. In Article 480 of the Criminal Code concerning receiving goods, if understood from its elements, namely